A Prism Method for Optical Glomerular Mapping of the Medial Olfactory Bulb in Mice - Homma, Ryota; Nagayama, Shin (Frontiers in Neural Circuits, 2019)
The processing of odor input in the brain begins in the olfactory bulb (OB), where odor information is represented by combinations of active glomeruli. Each glomerulus is associated with a specific odorant receptor type, of which there are ~1,000 in mice; thus different odors activate different subsets of glomeruli. Most receptor types have duplicate lateral and medial glomeruli in each of the left and right OBs. The two sets of glomeruli form separate but mirror-symmetric glomerular maps. It is not known whether the odor representations in these paired maps are exact copies of each other or potentially encode additional information. Previous studies of glomerular odor representations were mostly limited to the lateral map because the medial map is inaccessible with high-resolution activity mapping techniques, such as optical imaging. To address this, we developed a method for optical imaging of the medial bulb by replacing the contralateral bulb with a right-angle prism that has a mirror coating on the hypotenuse. With this method, we performed calcium imaging of corresponding subsets of glomeruli in the lateral map at the dorsal surface and the medial map at the medial wall. Thus, we demonstrate an experimental model system for comparing odor representations in these redundant sensory maps, enabling a better understanding of the role of paired maps and the neuronal coding of odor stimuli.